In vitro and in silico studies reveal capsid-mutant Porcine circovirus 2b with novel cytopathogenic and structural characteristics - Cruz, Taís Fukuta [UNESP]; Magro, Angelo José [UNESP]; de Castro, Alessandra M.M.G.; Pedraza-Ordoñez, Francisco J.; Tsunemi, Miriam Harumi [UNESP]; Perahia, David; Araujo, João Pessoa [UNESP] (Elsevier, 2018)
Porcine circovirus 2 (PCV2) is an icosahedral, non-enveloped, and single-stranded circular DNA virus that belongs to the family Circoviridae, genus Circovirus, and is responsible for a complex of different diseases defined as porcine circovirus diseases (PCVDs). These diseases – including postweaning multisystemic wasting syndrome (PMWS), enteric disease, respiratory disease, porcine dermatitis and nephropathy syndrome (PDNS), and reproductive failure – are responsible for large economic losses in the pig industry. After serial passages in swine testicle (ST) cells of a wild-type virus isolated from an animal with PMWS, we identified three PCV2b viruses with capsid protein (known as Cap protein) cumulative mutations, including two novel mutants. The mutant viruses were introduced into new ST cell cultures for reisolation and showed, in comparison to the wild-type PCV2b, remarkable viral replication efficiency (> 1011 DNA copies/ml) and cell death via necrosis, which were clearly related to the accretion of capsid protein mutations. The analysis of a Cap protein/capsid model showed that the mutated residues were located in solvent-accessible positions on the external PCV2b surface. Additionally, the mutated residues were found in linear epitopes and participated in pockets on the capsid surface, indicating that these residues could also be involved in antibody recognition. Taking into account the likely natural emergence of PCV2b variants, it is possible to consider that the results of this work increase knowledge of Circovirus biology and could help to prevent future serious cases of vaccine failure that could lead to heavy losses to the swine industry.
Keywords: Amino acid mutations; Cap protein; Molecular modeling; PCV2b mutants; Porcine circovirus; Viral replication